2020
DOI: 10.3389/fphar.2020.581011
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Kinase (HCK) Is Essential for NLRP3 Inflammasome Activation and Lipopolysaccharide-Induced Inflammatory Response In Vivo

Abstract: Activation of the NLRP3 inflammasome results in caspase 1 cleavage, which subsequently leads to IL-1b and IL-18 secretion, as well as pyroptosis, and aberrant activation of the inflammasome is involved in several diseases such as type 2 diabetes, atherosclerosis, multiple sclerosis, Parkinson's disease, and Alzheimer's disease. NLRP3 activity is regulated by various kinases. Genetic and pharmacological inhibition of the hematopoietic cell kinase (HCK), a member of the Src family of non-receptor tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…However, we found no difference in NFB signaling across our allelic series of HCK mutant macrophages following treatment with LPS or IL-4 to stimulate polarization. While this suggests that HCK does not regulate TAM polarization via the canonical NFB signaling cascade as proposed for PI3K, previous studies indicate an essential role for HCK in mediating the transcription of inflammatory cytokines and chemokines via activation of TLR4 and NLRP3 (43,44). Alternative macrophage polarization is also induced by STAT3/STAT6 activity (10), while STAT3 deficiency (or inhibition of STAT3-dependent signaling) is associated with increased expression of type I IFN response genes, including Cxcl9 and Cxcl10 (45,46).…”
Section: Discussionmentioning
confidence: 82%
“…However, we found no difference in NFB signaling across our allelic series of HCK mutant macrophages following treatment with LPS or IL-4 to stimulate polarization. While this suggests that HCK does not regulate TAM polarization via the canonical NFB signaling cascade as proposed for PI3K, previous studies indicate an essential role for HCK in mediating the transcription of inflammatory cytokines and chemokines via activation of TLR4 and NLRP3 (43,44). Alternative macrophage polarization is also induced by STAT3/STAT6 activity (10), while STAT3 deficiency (or inhibition of STAT3-dependent signaling) is associated with increased expression of type I IFN response genes, including Cxcl9 and Cxcl10 (45,46).…”
Section: Discussionmentioning
confidence: 82%
“…Lyn has been validated for specific increases in protein levels in human psoriatic lesions and is involved in regulating the expression of STAT3 and the NF-κB pathway to mediate a chronic inflammatory syndrome resembling human psoriasis in a mouse model by pan-genomic profiling ( Marchetti et al, 2009 ). Hck, a member of the Src family of kinases, is highly expressed in macrophages and is related to various inflammatory responses ( Kong et al, 2020 ). Clinical evidence has shown that the mRNA level of Prkcb in the bone marrow is significantly higher in patients with psoriasis than in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of expression with NCFs and TIMER database results indicate that these three genes are strongly related to SPI1, HCK, VAV1, CD53, ITGB2, and so on. According to the results of KEGG pathway enrichment, they are mainly involved in inflammation and immune response or tumorigenesis [42][43][44][45][46]. Our results show that NCFs and their coexpressed genes, including SPI1, HCK, VAV1, CD53, and ITGB2, are significantly associated with tumorinfiltrating immune cells, especially with immunosuppressive It is worth mentioning that when exploring the markers related to NCFs and immune cells, we found that NCFs showed a strong correlation with M2 macrophages and tumor-associated macrophages, but not with M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%